BNP as a New Biomarker of Cardiac Thyroid Hormone Function - Wang, Kaihao; Ojamaa, Kaie; Samuels, Abigail; Gilani, Nimra; Zhang, Kuo; An, Shimin; Zhang, Youhua; Tang, Yi-Da; Askari, Bardia; Gerdes, Anthony Martin (Frontiers in Physiology, 2020)
Background: Cardiac re-expression of fetal genes in patients with heart failure suggests the presence of low cardiac tissue thyroid hormone (TH) function. However, serum concentrations of T3 and T4 are often normal or subclinically low. Should that be the chosen direction, a serum biomarker for low cardiac TH function is needed to guide treatment of these patients. The clinical literature suggests that serum Brain Natriuretic Peptide (BNP) levels are inversely associated with serum triiodo-L-thyronine (T3) levels. The objective of this study was to investigate BNP as a potential serum biomarker for TH function in the heart. Methods: Two animal models of thyroid hormone deficiency: (1) 8-weeks of propyl thiouracil-induced hypothyroidism (Hypo) in adult female rats were subsequently treated with oral T3 for 3, 6, or 14 days; (2) heart failure induced by coronary artery ligation (myocardial infarction, MI) in adult female rats were treated daily with oral T3 for 8 and 16 weeks. Results: Six days of T3 treatment of Hypo rats normalized most cardiac functional parameters. Serum levels of BNP increased 5-fold in Hypo rats, while T3 treatment normalized BNP by day 14. Myocardial BNP mRNA was increased 2.5-fold in Hypo rats and its expression was decreased over time by T3 treatment. In MI rats, serum BNP was elevated 4.5-fold, while BNP was decreased in T3 treated animals. Myocardial BNP mRNA was increased 5-fold in MI rats and normalized by T3. Conclusions: Results from the two models of TH dysfunction confirmed an inverse relationship between tissue and serum T3 and BNP, such that the reduction in serum BNP could potentially be utilized to monitor efficacy and dosing of T3 treatment. Thus, serum BNP may serve as a reliable biomarker for cardiac TH function.